Penyuluhan Hukum Penyalahgunaan Media Sosial Pada Generasi Muda - Julianto Jover Jotam Kalalo; Zegovia Parera; Salvadoris Pieter (AIWADTHU: Jurnal Pengabdian Hukum, 2022)
Introduction: The modern era is full of information transparency and current technology, there are problems faced by everyone, including adults and also the younger generation among high school students (High School).Purposes of Devotion: The existence of writing this article is to instill knowledge related to the use of social media that is good and right and the legal implications that arise if social media is used incorrectly for teachers and students at SMA Negeri 1 Kurik, Merauke Regency. Method of Devotion: The legal counseling activity at SMA Negeri 1 Kurik, Merauke Regency was carried out using the panel discussion method in which the presenters took turns presenting the material then followed by a question and answer session between the presenters and students and teachers.Results of the Devotion: The lack of knowledge and understanding of the community and among high school students (Students) at this time that there is a legal provision (the ITE Law). So it is hoped that students will get more benefits from this activity, namely preventing students from participating in spreading hoax news, hate speech, accessing pornographic content, or other sites that have a negative impact on the growth and development of the younger generation.